Synthesis of Novel α,β-Unsaturated Sulfonic Acid Derivatives Containing Dithiocarbamate/Xanthate Groups by Ring Opening of an α,β-Unsaturated γ-Sultone - Khalili Foumeshi, Maryam; Ziyaei Halimehjani, Azim; Beier, Petr (Synlett, 2020)
An efficient method is disclosed for the synthesis of novel α,β-unsaturated sulfonic acid derivatives containing dithiocarbamate/xanthate groups through ring opening of an α,β-unsaturated γ-sultone with dithiocarbamic acid salts or xanthates prepared in situ. Treatment of the primary products with hydrochloric acid afforded the corresponding β-chloro-γ-(dithiocarbamato)propanesulfonic acids in excellent yields.
Keywords: dithiocarbamates; sultones; xanthates; sulfonic acids; nucleophilic substitution; propene sultone